PLASTIC LEARNING AND SUSTAINABILLITY TRAINING IN ELEMENTARY SCHOOL - IX, Mahasiswa KKN Labuhan Ratu (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Ecobricks are plastic bottles filled densely with non-biological waste, namely plastic. The technique is simple and very easy, therefore it can spread quickly through social networks (communities, villages, schools, etc.). The aim of ecobricks itself is to reduce plastic waste, and recycle it using plastic bottles to make something useful. This article attempts to provide an overview and explanation regarding the work program for making compost, including the process, stages, results and benefits. This article was written using a qualitative approach with a descriptive-explanatory model. As a result, students succeeded in making 12 ecobricks using around 2 kg of plastic waste collected from the school, village and each student's home. During the training, students showed high enthusiasm, as seen from their participation in discussions and practices. Even after the training was completed, several students showed initiative in making ecobricks at home and invited their families to participate. This article is limited to the implementation of Regular KKN Period II 2024. This article also contributes to biological science as well as practices and strategies for implementing SDGs points.